The Effect of Cawthorne and Cooksey Training program on Static and Dynamic Balance of Women with Multiple Sclerosis - hamid zahedi; Fahimeh Shafeai (Sport Sciences and Health Research)
Balance difficulties are common among multiple sclerosis patients. The aim of this study was to investigate the effect of Cawthorne and Cooksey training on static and dynamic balance of women with multiple sclerosis (MS). The population consisted of women suffering from multiple sclerosis and their disability index (EDSS) was three to six. 30 participants who were eligible to enter the research were purposively selected and randomly assigned to control and experimental groups (15 subjects per group). In order to measure the static balance, Sharpened Romberg balance test, and to measure the dynamic balance, Berg balance test were used. To analyze the data, independent t test and analysis of variance with repeated measures with SPSS 19 were used. The results showed that Cawthorne and Cooksey training had significant differences in static and dynamic balance of participants. Therefore, it is recommended to use this type of training to improve balance in patients with multiple sclerosis.